Acetabular revision in total hip arthroplasty with tantalum augmentation and lyophilized bovine xenograft - Cristiano Valter Diesel; Tiango Aguiar Ribeiro; Marcelo Reuwsaat Guimarães; Carlos Alberto de Souza Macedo; Carlos Roberto Galia (Revista Brasileira de Ortopedia)
Abstract Objective To evaluate a mixed technique of acetabular reconstruction, which uses trabecular metal in the form of tantalum augments associated with lyophilized bovine xenograft. Methods Fifteen patients were evaluated prospectively, who underwent acetabular reconstruction with impacted lyophilized bovine xenograft associated with the use of tantalum augments. The main outcome was the failure of the tantalum-bone interface. Results The population had a mean age of 58.33 years ± 14.27; the majority was female, 80%. Of the total subjects, 66.7% were operated for failure in primary arthroplasty. The mean follow-up time was 45.2 months ± 11.39. The failure rate of the method in the period and population studied was 6.7%. Conclusion An extremely high index (93.3%) of success was observed in an average time of 45.2 months of follow-up. Data were comparable to current literature, demonstrating that the technique employed and proposed is adequate for hip reconstruction in young patients.